The Effectiveness of Sitting Position with Dangling Legs on Dyspnea in Chronic Heart Failure Patients - Nur Asnah Sitohang; Nurul Huda Afifah (Indonesian Journal of Global Health Research, 2025)
Chronic Heart Failure (CHF) is one of the leading causes of morbidity and mortality worldwide, with dyspnea being the most common symptom resulting from increased pulmonary venous pressure and pulmonary edema. Non-pharmacological interventions such as positioning, particularly the sitting position with legs hanging down, have been reported to effectively reduce dyspnea in patients with CHF. This manuscript aims to analyze the effectiveness of the sitting position with legs hanging down in reducing dyspnea perception and improving vital parameters. The research method used a single case study design with interventions applied to one CHF patient. Data were collected through interviews, observations, physical examinations, and medical documentation studies. Pain intensity was measured using a Visual Analog Scale (VAS), while respiratory and oxygenation parameters were assessed descriptively. The intervention results showed a decrease in respiratory rate from 24 to 18 breaths per minute and an increase in oxygen saturation from 96% to 98% within three days, accompanied by reduced dyspnea scores and improved breathing comfort. These findings indicate that the sitting position with legs hanging down is a simple, effective intervention that can be integrated into evidence-based nursing practices for patients with CHF.